GnRH Agonist Trigger and LH Activity Luteal Phase Support versus hCG Trigger and Conventional Luteal Phase Support in Fresh Embryo Transfer IVF/ICSI Cycles—A Systematic PRISMA Review and Meta-analysis - Haahr, Thor; Roque, Matheus; Esteves, Sandro C.; Humaidan, Peter (Frontiers in Endocrinology, 2017)
Introduction The use of GnRHa for final oocyte maturation trigger in oocyte donation and elective frozen embryo transfer cycles is well established due to lower ovarian hyperstimulation syndrome rates (OHSS) as compared to hCG trigger. A recent Cochrane meta-analysis concluded that GnRHa trigger was associated with reduced live birth rates in fresh autologous IVF cycles compared to hCG trigger. However, the evidence is not unequivocal, and recent trials have found encouraging reproductive outcomes among couples undergoing GnRHa trigger and individualized luteal LH activity support. Thus, the aim was to compare GnRHa trigger followed by luteal LH activity support with hCG trigger in IVF patients undergoing fresh embryo transfer. Material and methods We conducted a systematic review and meta-analysis of randomized trials published until December 14th, 2016. The population was infertile patients submitted to IVF/ICSI cycles with GnRH antagonist co-treatment who underwent fresh embryo transfer. The intervention was GnRHa trigger followed by LH activity luteal phase support. The comparator was hCG trigger followed by a standard luteal phase support. The critical outcome measures were live birth rate and OHSS rate. The secondary outcome measures were: number of oocytes retrieved, clinical and ongoing pregnancy rates, and miscarriage rates. Results A total of five studies met the selection criteria comprising a total of 859 patients. The live birth rate was not significantly different between the GnRHa and hCG trigger groups (OR 0.84, 95% CI 0.62, 1.14). OHSS was reported in a total of 4/413 cases in the GnRHa group compared to 7/413 in the hCG group (OR 0.48, 95% CI 0.15, 1.60). We observed a slight, but non-significant increase miscarriage rate in the GnRHa triggered group compared to the hCG group (OR 1.85; 95% CI 0.97, 3.54). Conclusion GnRHa trigger with LH activity luteal phase support resulted in comparable live birth rates compared to hCG trigger. The most recent trials reported live birth rates close to unity indicating that individualization of the LH activity luteal phase support improved the luteal phase deficiency reported in the first GnRHa trigger studies. However, LLS optimization is needed to further limit OHSS in normo-responder patients